DEVELOPING OF WEB-BASED GRAVE SOFTWARE PROTOTYPE - Katri Widayani; Sumiarti Sumiarti; Nunie Nurida (UIN Syarif Hidayatullah Jakarta, 2017)
Jakarta has 65.000 hectares ofland area, homes to 9.9 million Jakarta populations, 98 hectares of grave land, and mortality rate of 0.64%. Those facts make the availability of graveyard becoming critical. To overcome the problem of high mortality rate and limited grave area, it is ideal to use Joint Corpse System, that is a grave filled with more than one corpse. Currently, registering a grave tomb in Jakarta is still using manual system, that is when a family member dies, the remaining family must come to the Public Cemetary office to fill out the registration form and choose the available tomb. However, the traffic jam in Jakarta makes it difficult for people to register the grave, for the Cemetery officer to inform the people regarding with the cemetery, and for the heirs whose leases have expired. Therefore, it is important to develop a web-based grave management information system in order to make people easier to reserve the tomb. The web gives people a complete information about grave location and how to register the grave which can be accessed using internet. The study aims to build a web-based information management system for grave registration with Tanah Kusir Public Cemetary as the object of the research. The study uses Prototyping Method, which analyzes the need system to see all components used by the running system and the developing one. The analysis also includes documenting the information system activity such as Input, Processing, Output, Storage, Controlling, Inteface design, Menu Program, and Database. Coding, is the stage of translating the results of analysis and design into the PHP programming language in order to develop a software. The result of the study is people can access the cemetary information, register and confirm via the internet. The cemetary official can also display available tombs in realtime.